Nitrogen management in poultry industry from circular economy perspective - Chia, Pei Wen (2022)
The intensive production and linear economy (LE) model utilisation in Malaysian poultry industry potentially lead to climate change. The negative impacts of climate change on poultry farming have attracted the attention of the government because it induces the need to have a transition from a LE model to a circular economy (CE) model. Determining the degree of circularity in an industry is fundamental for identifying the barriers and stimulating strategic planning to implement the CE model. This research measured the degree of circularity in the poultry industry with nitrogen life cycle assessment (LCA). The outline of the nitrogen flows in the Sankey Diagram showed that the industry operates in a combination of a LE model and a CE model. 42.34% of nitrogen was lost to the environment and 28.06% of nitrogen was recovered to generate electricity and produce animal feed meal and organic fertilisers. The nitrogen materials were mostly lost through ammonia emission, nitrate runoff as well as waste disposal and wastewater discharge without treatment. Issues with respect to ineffective implementation and governance mechanism, imbalanced industrial development, limited financial capacity from local financial institutions and lack of a supportive enabling environment have limited the progress of circularity improvement. In return, the recommendations such as the introduction of an appropriate governance structure and regulatory framework, closing the industrial development gap, budget reinforcement and enabling environment strengthening were proposed to solve the identified barriers and facilitate the poultry farmers in the economy model transition. Besides, the smart farming activities, namely feed ingredients substitution with palm kernel cake, by-products recycling in rendering plant, alum addition in beddings, Amolgera addition in litter pile and microalgae cultivation in wastewater and sludge treatment are revealed as the potential approaches to reduce the nitrogen loss as well as embracing a CE model in the poultry industry.